(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, it has been studied that it is important to form the unique characteristics of the child’s linguistic personality with a colorful landscape, the comprehensive development of primary school students, and the fact that speech is rich and flawless in the education of a mature generation